Improved Event-Based Pi Controller for Limit Cycles Avoidance - Md Yusop, Noraide; Mamat, Rosbi (International Journal of Integrated Engineering, 2021)
One of the issues in designing event-based proportional-integral (PI) controller using aggressive tuning rules is the possible occurrence of limit cycles. To date, there is no adequate simple event-based PI controller technique able to explicitly use aggressive tuning rule. In this paper an improved simple event-based PI controller is proposed to address this issue. By analysing the discrete PI algorithm, an improved triggering condition is introduced. To test the effectiveness of the approach, extensive simulations are carried out by introducing the proposed method to process control under various sampling period, triggering limit, and different tuning rules namely, AMIGO, SIMC and One-Third tuning rules. The performances are evaluated based on two standard criteria: ability to imitate the time-triggered system and computation load reduction.  The results show that the performance of the proposed method able to surpass others simple event-based PI controller approaches by giving a closest response to the time-triggered system, lowest computational load and able to avoid the limit cycles occurrences. It is envisaged that the proposed method can be useful in designing a simple event-based PI controller that compatible with any type of tuning rules.